Clinical Characteristics of Melancholic and Nonmelancholic Depressions - Valerio, Marina Paula (2023)
This study aimed to compare clinical-demographic features of melancholic and nonmelancholic depressions. We included 141 depressed inpatients classified as melancholic and nonmelancholic by the Sydney Melancholia Prototype Index (SMPI) and Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) criteria. Results were controlled for confounders, including severity measures. Melancholic patients by both diagnostic systems were more severely depressed and presented more psychotic symptoms, neurological soft signs, and psychomotor disturbances. Melancholic patients classified by the SMPI were also older at illness onset and had fewer suicide attempts. After controlling for confounders, although all differences remained significant for SMPI diagnosis, the DSM-5 diagnosis of melancholia was only associated with further impaired motor sequencing. The results obtained with the SMPI support the hypothesis that melancholia has clinical features qualitatively different from those of nonmelancholic depressions. Contrarily, the DSM-5 specifier seems to reflect the severity of depressive episodes rather than core clinical features of melancholia.